2008
DOI: 10.1159/000127440
|View full text |Cite
|
Sign up to set email alerts
|

Non-Bone Marrow Origin of Neointimal Smooth Muscle Cells in Experimental In-Stent Restenosis in Rats

Abstract: Objective: To determine the contribution of bone marrow (BM)-derived cells in in-stent restenosis (ISR) and transplant arteriosclerosis (TA). Methods: Non-transgenic rats WT F344TG (n = 3) received stent implantation 6 weeks after lethal total body irradiation and suppletion with bone marrow from a R26-hPAP transgenic rat. After 4 weeks the abdominal aortas were harvested, the stent was quickly removed, the abdominal aorta was snap-frozen in liquid nitrogen and 5 µm cryosections for stainings were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Although we did not study the underlying mechanism(s) of enhanced ISR in diabetic BBDP rats yet, we suggest that long-term diabetes increases the proliferative and migratory capacity of medial and neointimal smooth muscle cells, thereby facilitating neointima formation [36, 37]. In addition, reduced endothelial repair capacity in diabetic BBDP rats might have contributed to enhanced ISR [38], but this needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not study the underlying mechanism(s) of enhanced ISR in diabetic BBDP rats yet, we suggest that long-term diabetes increases the proliferative and migratory capacity of medial and neointimal smooth muscle cells, thereby facilitating neointima formation [36, 37]. In addition, reduced endothelial repair capacity in diabetic BBDP rats might have contributed to enhanced ISR [38], but this needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore VSMClike cells originating from the BM, and perhaps also from adipose tissue, may play a pro-inflammatory role, rather than representing a pool of progenitor cells that will permanently differentiate into adult VSMCs. This might explain why we found that all BM-derived cells in the neointima after stenting expressed inflammatory cell markers [178]. The importance of such cells may of course be significant: the effect of AngII on stimulating the development of the VSMC-like cells that support or possess traits of inflammatory cells may be another example of the versatility of this peptide as a proinflammatory factor.…”
Section: Mscs With Vsmc Traitsmentioning
confidence: 91%
“…Progenitor cells isolated from the tunica media of mouse aortas by flow cytometry could acquire the phenotype of SMC in culture as measured by positivity for calponin, α-SMA and SM MHC [37]. The possibility of a stem cell niche in the vessel wall could be of importance in studies that report a non-BM-derived origin for cells in the neointima [5, 25-27, 29, 30, 38]. …”
Section: Origin Of Smc In Vascular Disease: Role Of Bm-derived Spcmentioning
confidence: 99%